2009
DOI: 10.1002/apj.337
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐industrial tests on enhanced underground coal gasification at Zhong‐Liang‐Shan coal mine

Abstract: A new process of enhanced underground coal gasification (EUCG) has been demonstrated recently in successful semi-industrial tests at Zhong-Liang-Shan (ZLS) coal mine in China. The EUCG is featured using manbuilt pinnate channels and controlled moving injection points along coal-bed channel to produce syngas through underground coal gasification (UCG). To optimize the EUCG process, this field trial was performed with various operational manoeuvres, such as implementing controlled moving injection points, O 2 -e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…16 also indicates that the LHV of the product gas had its highest value between 0.9 to 1.65 MPa and it seems that above around 2 MPa the LHV decreases which is in good agreement with the carbon conversion and CGE result. Furthermore this finding agrees with a semi industrial test conducted with a coking coal (60% F.C, 16% V.M., LHV 26 MJ/kg) gasified with air and steam, aiming to investigate the effect of cyclically changing the operational pressure in terms of the quality of the product gas [26]. The gas composition was 15-25 % CO, 5-8% CH 4 and 10-30% H 2 which is in good agreement with the gas composition produced at pressures in this study for CO and H 2 during the reduction zone as shown in Table 5 and Fig.…”
supporting
confidence: 87%
“…16 also indicates that the LHV of the product gas had its highest value between 0.9 to 1.65 MPa and it seems that above around 2 MPa the LHV decreases which is in good agreement with the carbon conversion and CGE result. Furthermore this finding agrees with a semi industrial test conducted with a coking coal (60% F.C, 16% V.M., LHV 26 MJ/kg) gasified with air and steam, aiming to investigate the effect of cyclically changing the operational pressure in terms of the quality of the product gas [26]. The gas composition was 15-25 % CO, 5-8% CH 4 and 10-30% H 2 which is in good agreement with the gas composition produced at pressures in this study for CO and H 2 during the reduction zone as shown in Table 5 and Fig.…”
supporting
confidence: 87%
“…In the Yanzhou coal mine in Shandong Province, China, there is a plan to carry out an underground coal gasification (UCG) industrial trial. The UCG is a mining technology that burns coal in a controlled manner for producing combustible gas, so the high-temperature gas flow in the combustion space area would bake the surrounding rocks by convective and radiative heat transfer and make the surrounding rocks reach about 1200 • C [61,62]. High temperatures would change the physical and mechanical properties of the granite layer above the coal seam, which affects its stability and the safety of the gasifier in the UCG stope.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are several [13][14][15][16][17] pilot plants for underground coal gasification combined with gas clean-up in China.…”
Section: Introductionmentioning
confidence: 99%